PENGARUH KOMPETENSI SUMBER DAYA MANUSIA (SDM), PENGEMBANGAN KARIR DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA BANK JAWA BARAT DAN BANTEN (BJB) CABANG RANGKASBITUNG - Ipan Hilmawan (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
This study aims to determine the effect of Human Resource Competence (X1), Career Development (X2) and Organizational Commitment (X3) on Employee Performance (Y) at Bank Jawa Barat and Banten (Bank Bjb) Rangkasbitung Branch. In this research, the method used is quantitative research. The population in this study were 86 employees of West Java and Banten Banks (Bank Bjb) Rangkasbitung Branch. The sampling technique in this study is saturated sampling, that is, all members of the population are used as samples. The data collection method in this research is using a questionnaire and analyzing the data using IBM SPSS version 25.00 for Windows. The research results obtained are: First, Human Resource Competence (HR) has a positive and significant effect on employee performance as evidenced by the value of tcount > ttable, which is 110.973 > 1.66. Second, Career Development has a positive and significant effect on employee performance as evidenced by the value of tcount > ttable, which is 11,695 > 1.66. Third, Organizational Commitment has a positive and significant effect on employee performance as evidenced by the value of tcount > ttable, which is 8.328 > 1.66.